An Ethnobotanical Study of Plants Used as Traditional Medicine and Its Processing in Gapura District, Sumenep, Madura - Niqrisatut Thibab; Luchman Hakim; Jati Batoro (Journal of Indonesian Tourism and Development Studies, 2022)
The aim of this study is to describe the variety of medicinal plants, the ingredients of medicinal plants, and its utilization in Gapura District, Madura Regency. This study was conducted on June – October 2021. This study methodology was started by collecting the data, observation, and documentation. This study consisted of 60 respondents aged over 35 years because they are more experienced in making traditional medicines. The analysis of data used UVS, FUVS, ICS, and SWOT. This study found that 37 of 30 families of medicinal plants were utilized by Gapura societies. Based on the results of FUVs (Family Use Value), the families that are often used by the people of Gapura District are Zingiberaceae with a percentage of 1.75%, and the Moringaceae family with a percentage of 0.5%. The commonly utilized plant organ is the rhizome which is processed using a grater. The strategy for conserving the diversity of medicinal plants in Gapura District is wild and cultivated. Wild plants are usually only considered pests by the local community, but some wild plants have very good potential to be used as traditional medicines. Cultivated plants are a way of processing medicinal plants with the aim of bringing maximum results with good quality. Furthermore, Gapura District made the farmers' community conserve the medicinal plants through biological conservation.